Thermal boundary condition analysis of cooling objects exposed to a free impinging jet using the heatline concept - Mostafa Mahdavi (Taylor & Francis Group, 2021)
Heat and flow pattern of a vertical free jet impinging on a hot disk were numerically investigated. A cylinder with various thicknesses and materials exposed simultaneously to uniform heat flux on one side and a free impinging jet on the other side is simulated by ANSYS Fluent 19.3. For simulations, the thermal boundary condition on the hot surface might differ due to the nature of the heat flow. The Volume of Fluid (VOF) approach is used to model the free jet heat transfer and fluid dynamics with the presence of air, while only the energy equation is solved in the cylinder. Heatline equation is solved to reveal the heat flow direction and effects of different geometry conditions. The maximum heat flux of 2.5 MW/m2 was obtained at the edge of stagnation region for hot target made of copper, while the value was 1.5 MW/m2 when the material was combined with stainless steel. However, the general thermal and hydrodynamic features of the jet flow were not influenced. It means that hot object condition may only affect the balance between heat flux and temperature, and the ideal uniform heat flux on the impinging wall may not be achieved in any experimental conditions.